VARIASI KERAGAMAN LINGUISTIK BAHASA ARAB DI NEGARA ARAB DAN IMPLIKASINYA DALAM PEMBELAJARAN BAHASA ARAB DI INDONESIA - Sofa, Ainur Rofiq; Sugianto, Muhammad (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
The diverse use of Arabic in Yemen, Egypt, Sudan, and the United Arab Emirates creates a linguistically rich context with variations in dialects, vocabulary, and communication styles. The implications of this diversity on Arabic language learning in Indonesia require a profound understanding, especially in the increasingly interconnected global context where diverse international communication skills are essential. This research aims to explore the implications of such diversity on the international communication abilities of Arabic language learners in Indonesia, focusing on grammar, vocabulary, and cultural context. Qualitative analysis using a literature review approach is employed to explore the variations in Arabic language usage in these four countries. The findings reveal significant differences in phrases related to agriculture, depicting variations in common greetings, general questions, the use of local dialect terms for "school," as well as variations in terms related to "food" or "dish," and terms related to plants, fruits, and trees. Despite the variations, the main findings reflect similarities in the use of formal greetings, general questions, and educational terms across the regions. The implications of these findings can contribute to designing more effective Arabic language learning strategies in Indonesia by considering this diversity.